Challenges and Solutions for Lumbar Total Disc Replacement Implantation. (15th December 2017) - Janssen, Michael; Garcia, Rolando; Miller, Lynn; Reed, William; Zigler, Jack; Ferko, Nicole; Hollmann, Sarah
Abstract : N/A: Long-term data are now available to support the safety and efficacy of lumbar total disc replacement (TDR). Five-year randomized and controlled trials, meta-analyses, and observational studies support a similar or lower risk of complications with lumbar TDR compared with fusion. The panel concluded that published data on commercially available lumbar TDR devices demonstrate minimal concerns with late-onset complications, and that the risk of adjacent segment degeneration and reoperations can be reduced with lumbar TDR versus fusion. Survey results of surgeon practice experiences supported the evidence, revealing a low rate of complications with TDR. Panelists acknowledged the importance of adhering to selection criteria to help minimize patient complications.